Dysregulation of Myelopoiesis by Chronic Alcohol Administration During Early SIV Infection of Rhesus Macaques. (18th June 2014) - Siggins, Robert W.; Molina, Patricia; Zhang, Ping; Bagby, Gregory J.; Nelson, Steve; Dufour, Jason; LeCapitaine, Nicole J.; Walsh, Cullen; Welsh, David A.
<x xml:space="preserve">Abstract</x> Background Chronic alcohol intoxication suppresses immune function and increases osteoporosis risk suggesting bone‐tissue cytotoxicity. Human immunodeficiency virus infection leads to similar impairments. This study investigated the effects of chronic alcohol administration during the early stage of simian immunodeficiency virus (SIV) infection on hematopoietic stem and progenitor cells (HSPCs) and their differentiated progeny in the bone marrow and peripheral blood of rhesus macaques. Methods Rhesus macaques were administered alcohol or sucrose daily for a period of 3 months prior to intrarectal inoculation with 250 TCID50 of SIVmac251. Bone marrow aspirates and blood samples were taken prior to and 2 weeks after SIV infection. Bone marrow cells (BMCs) were assessed using flow cytometric phenotyping for upstream HSPCs and for differentiated cells of the monocyte‐granulocyte lineages. Likewise, cells were quantitated in peripheral blood. Results Of the bone marrow HSPCs, only the common lymphoid progenitor (CLP) was altered by alcohol administration pre‐SIV (38 ± 9.4/106 BMCs vs. 226 ± 64.1/106 BMCs, sucrose vs. alcohol). Post‐SIV, the frequency of CLPs in the bone marrow of alcohol‐administered macaques decreased compared with the sucrose‐administered macaques (107 ± 47.6/106 BMCs vs. 43 ± 16.3/106 BMCs). However, marrow mature cells of the monocyte lineage, specifically macrophages and osteoclast progenitors, were increased by both chronic alcohol administration and SIV infection (287% and 662%, respectively). As expected, mature cells such as granulocytes (polymorphonuclear cells), B cells, and CD4+ T cells in the peripheral blood were decreased by SIV infection (37 to 62% decline from preinfection), but not affected after 3 months of chronic alcohol administration. Conclusions Chronic alcohol administration disrupts myelomonocytic development in the bone marrow during the early period of SIV infection promoting macrophage and osteoclast lineages. We predict this shift in CLP:macrophage/osteoclast balance creates an environment that favors bone resorption and immunosuppression.